BENTUK, FUNGSI DAN MAKNA MOTIF CARANO KERAJAAN SIGUNTUR DI DHARMASRAYA - Nur Fitri Handayani, Dra. Jupriani, M.Sn, Drs. Wisdiarman, M.Pd (Universitas Negeri Padang, 2013)
The purpose of this study is to describe 1) Carano motif form in the Siguntur Kingdom, 2) Carano motif functions in the Siguntur Kingdom, 3) Carano motif meaning in the Siguntur Kingdom. This research uses descriptive qualitative method. Sources of data in this study were obtained form two types of data are primary data, in the form of oral testimony of a royal heir Siguntur and expert carving patterns, secondary data is a written document in the form of photographs and literature. Data collection procedures through observation, interview and documentation. Data analysis was performed with data collection, data reduction, data classification, data display and conclusion. Checking the validity of the findings made by the technique of triangulation. Our results are found to form, function and meaning carano motif in the Kingdom Siguntur Dharmasraya. Key words : Form, function, meaning, motif, carano.